Research in organizational change and development. Vol. 16 - Woodman, Richard W.; Pasmore, William A. (Research in organizational change and development, 2007)
The Research in Organizational Change and Development series is an outlet for cutting edge conceptual and empirical scholarly contributions that have the capacity to shape research and practice. The field of organizational change and development continues to evolve rapidly, as the demand for rapid and effective organizational transformation has increased. It is more important that ever that scholars address topics such as increasing intervention effectiveness, managing emotional issues raised during change, measuring the impact of change, and improving the methods we use to conduct research on organizational change. This series provides a definitive outlet for the most thoughtful and exciting work of newly emerging and well-recognized scholars in the field of organization change and development. This series regularly invites leading thinkers in the field to present their latest models, empirical findings and thoughtful directions for future research. This series provides historical overviews of different paradigms of research in the field.